2023
DOI: 10.1002/advs.202206344
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RPA1 Impairs Peripheral T Cell Homeostasis and Exacerbates Inflammatory Damage through Triggering T Cell Necroptosis

Abstract: The peripheral T cell pool is maintained at dynamic homeostasis through fine-tuning of thymic output and self-renewal of naïve T cells. Lymphopenia or reduced lymphocyte number is implicated in autoimmune diseases, yet little is known about the homeostatic mechanisms. Here, it is reported that the replication protein A1 (RPA1) plays a critical role in T cell homeostasis. Utilizing T cell-specificRpa1-deficient (Rpa1 fl/fl Cd4-cre) mice, loss of Rpa1 results in lymphopenia through restraining peripheral T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…DAI binds to several types of cytoplasmic DNA to activate IFNs production via the TBK1–IRF3 axis, which makes it necessary for the response of endogenous aberrant DNA [ 138 ]. Significantly, a recent study showed that ZBP-1-RIPK3 signaling that caused T cell necroptosis is stimulated by knocking down RPA1, suggesting that ZBP-1 may function as a positive sensor for DNA damage [ 139 ]. Retinal pigment epithelial cells consistently expressed significant levels of ZBP-1 in response to oxidative stress-induced mtDNA accumulation [ 140 ].…”
Section: The Regulation Of Innate Immune Sensors By Ddr Componentsmentioning
confidence: 99%
“…DAI binds to several types of cytoplasmic DNA to activate IFNs production via the TBK1–IRF3 axis, which makes it necessary for the response of endogenous aberrant DNA [ 138 ]. Significantly, a recent study showed that ZBP-1-RIPK3 signaling that caused T cell necroptosis is stimulated by knocking down RPA1, suggesting that ZBP-1 may function as a positive sensor for DNA damage [ 139 ]. Retinal pigment epithelial cells consistently expressed significant levels of ZBP-1 in response to oxidative stress-induced mtDNA accumulation [ 140 ].…”
Section: The Regulation Of Innate Immune Sensors By Ddr Componentsmentioning
confidence: 99%